Unraveling electrochemical performance of magnesium vanadate-based nanostructures as advanced cathodes for rechargeable aqueous zinc-ion batteries - R. Shanthappa; Ashok Kumar Kakarla; Hari Bandi; Wasim Akram Syed; Jae Su Yu (Journal of Magnesium and Alloys)
High-performance aqueous zinc (Zn)-ion batteries (AZIBs) have emerged as one of the greatest favorable candidates for next-generation energy storage systems because of their low cost, sustainability, high safety, and eco-friendliness. In this report, we prepared magnesium vanadate (MgVO)-based nanostructures by a facile single-step solvothermal method with varying experimental reaction times (1, 3, and 6 h) and investigated the effect of the reaction time on the morphology and layered structure for MgVO-based compounds. The newly prepared MgVO-1 h, MgVO-3 h and MgVO-6 h samples were used as cathode materials for AZIBs. Compared to the MgVO-1 h and MgVO-6 h cathodes, the MgVO-3 h cathode showed a higher specific capacity of 492.74 mA h g-1 at 1 A g-1 over 500 cycles and excellent rate behavior (291.58 mA h g-1 at 3.75 A g-1) with high cycling stability (116%) over 2000 cycles at 5 A g-1. Moreover, the MgVO-3 h electrode exhibited good electrochemical performance owing to its fast Zn-ion diffusion kinetics. Additionally, various ex-situ analyses confirmed that the MgVO-3 h cathode displayed excellent insertion/extraction of Zn2+ ions during charge and discharge processes. This study offers an efficient method for the synthesis of nanostructured MgVO-based cathode materials for high-performance AZIBs.